Load Effect Analysis on Single-Phase AC Voltage Regulator for Enhanced Power System Performance - Mochammad Nawal Gibran; Anggara Trisna Nugraha; Salsabila Ika Yuniza (Journal of Marine Electrical and Electronic Technology, 2023)
The Single-Phase AC Voltage Regulator plays a pivotal role in controlling the root mean square (RMS) output voltage (Vrms output​) for various applications, including motor speed control and power modulation in electrical systems. The regulation of Vrms​ is achieved by adjusting the firing angle of the power switch, which introduces a delay in the output voltage waveform. Consequently, this type of voltage regulator is often referred to as a phase delay controller. This study investigates the performance of a full-wave single-phase AC voltage regulator under various load conditions using Silicon Controlled Rectifiers (SCR). The research employs a simulation-based approach using PSIM software to model and analyze the current and voltage waveforms, offering insights into the dynamic behavior of the system under resistive, inductive, and mixed load variations. The findings provide a deeper understanding of the load effects on voltage regulation efficiency, highlighting the importance of optimizing regulator design for enhanced performance and reliability in real-world applications.